PERBEDAAN SIKAP AKUNTAN PUBLIK DAN PENGGUNA JASA AKUNTAN PUBLIK TERHADAP ADVERTENSI JASA AKUNTAN PUBLIK - ARLEEN HERAWATY; NICKEN DESTRIANA (Jurnal Bisnis dan Akuntansi, 2010)
The purpose of this study is to analyze the difference attitude of public accountants and clients toward advertising of public accountant’s services. This research were using 203 respondents, divide into two groups. There were 125 respondents who worked as public accountant, and 78 respondents who work in companies at managerial level. Attitude was measured by seven aspects such as image of auditor’s perception, service quality, service price, clients’ awareness, sizes of public accountant, firm public accountant firm competitiveness, and government’s influence. Mann-Whitney U Test was used to analyze the hypothesis. The result of this research showed that image of auditor’s perception ,service quality, and client’s awareness have significant different attitude among public accountants and client’s of public accountants. On the other hand, service price, sizes of public accountant, firm public accountant firm competitiveness, and govern-ment’s influence do not have significant different attitude among public accountants and client’s of public accountants.